2022
DOI: 10.3389/fpls.2022.983786
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analysis of cupin_1 domain-containing members involved in the responses to Sclerotinia sclerotiorum and abiotic stress in Brassica napus

Abstract: Cupin_1 domain-containing proteins (CDPs) are ubiquitously present in higher plants, which are known to play essential roles in various biological processes. In this study, we carried out genome-wide characterization and systematic investigation of the CDP genes in Brassica napus. A total of 96 BnCDPs, including 71 germin-like proteins (GLPs; proteins with a single cupin_1 domain) and 25 CDP bicupins (proteins with two cupin_1 domains), were identified and clustered into six distinct subfamilies (I–VI) based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Among them, the bicupins in DlCDP family all belong to the branch VII b, and these members have longer exon lengths (Figure 2). This may be due to the number of cupin_1 domains greatly affects the exon length and motif type of DlCDPs, which was also observed in rapeseed (He et al, 2022). Accordingly, the expression pattern of DlCDPs showed that bicupin member DlCDP49 had a low expression level in well-developed tissues (Figure 7).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Among them, the bicupins in DlCDP family all belong to the branch VII b, and these members have longer exon lengths (Figure 2). This may be due to the number of cupin_1 domains greatly affects the exon length and motif type of DlCDPs, which was also observed in rapeseed (He et al, 2022). Accordingly, the expression pattern of DlCDPs showed that bicupin member DlCDP49 had a low expression level in well-developed tissues (Figure 7).…”
Section: Discussionmentioning
confidence: 87%
“…CDP family includes GLP members that contain a single cupin_1 domain, which are related to hormone-mediated development processes ( Murphy and Peer, 2022 ). GLPs have been identified in multiple species ( Davidson et al., 2010 ; Cheng et al., 2014 ; Li et al., 2016 ; Zhang et al., 2022 ; Li et al., 2023 ), and whole CDP family members have also been identified in B. napus ( He et al., 2022 ). In our cognition, the distribution and functional diversity of CDP family in ma bamboo have not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome data were obtained from the previous studies that included a total of 32 tissues containing bud, callus, leaf, stamen, new pistil, blossomy pistil, wilting pistil, stem, sepal, ovule, 11 time-course seeds and silique walls (0, 4,8,12,16,20,24,28,32,40,48), and five stress conditions (Sclerotinia sclerotiorum (S. sclerotiorum), dehydration, salt, cold, and abscisic acid) [45][46][47]. These data were aligned to the reference genome by software hisat2 with the following parameters: -t -p 40-min-intronlen 20-max-intronlen 20,000-dta [48], and the expression quantity based on the transcripts per kilobase million (TPM) normalization method was calculated by software Stringtie with the setting: -e -B -p 30 -f 0.1 [49].…”
Section: Analysis Of the Expression Pattern Of Bnsrs In Different Tis...mentioning
confidence: 99%